Nocturnal systolic hypertension is a risk factor for cardiac damage in the untreated masked hypertensive patients. Issue 11 (26th September 2019) - Li, Jianhao; Cao, Yalin; Liu, Chen; Li, Jiayong; Yao, Fengjuan; Dong, Yugang; Huang, Huiling
Abstract: The nocturnal blood pressure (BP) has been identified as a prognostic factor for cardiovascular events. This study aimed to investigate the association between different patterns of nocturnal masked hypertension (MH) and the echocardiographic parameters in the untreated nocturnal MH patients. A total of 721 untreated MH patients (309 females and 412 males, mean age = 56.59 ± 15.20 years) from June 2006 and June 2016 were included and divided into nocturnal systolic MH (n = 77), nocturnal diastolic MH (n = 232), and nocturnal systolic/diastolic MH (n = 412) groups according to the ambulatory blood pressure monitoring. Baseline characteristics, office BP values, ambulatory BP monitoring parameters, and echocardiographic parameters were compared among the three groups. The independent factors associated with echocardiographic parameters were analyzed by multivariate linear regression. The nocturnal systolic group had the highest ratio of males, mean age, and office systolic BP (SBP), and the lowest office, 24‐hour, daytime, nocturnal diastolic BP and heart rate among the three groups. The nocturnal diastolic group had the lowest interventricular septum (IVS) thickness, left atrium (LA) dimension, and left ventricular (LV) mass among the three groups. Multivariate linear regression analysis revealed that 24‐hour, daytime, and nocturnal SBPs were all positively associated with LA dimension, IVS thickness, and LV mass (all B were positive and P < .050). Pearson's correlation analysis showed that nocturnal SBP was positively correlated with LA dimension, IVS thickness, and LV mass. These results suggested that different patterns of nocturnal MH had different echocardiographic outcomes. Nocturnal SBP was the independent factor associated with the echocardiographic parameters.